Pengaruh Model Pembelajaran POE (Predict-Observe-Explain) Berorientasi Chemoentrepreneurship Terhadap Pemahaman Konsep Siswa Pada Materi Larutan Penyangga - Andriani, Reni; Muhali, Muhali; Dewi, Citra Ayu (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Buffer solution is a material that requires a fairly high analysis with an understanding of concepts that must be understood by students and requires practice in everyday life. Learning will be more meaningful and provide a deep understanding to the learner if the learning is adapted to the characteristics of the subject matter. One effective solution is to apply the learning model POE (Predict- Observe-Explain) oriented Chemoentrepreneurship. The aim of this research was to evaluatethe influence of learning model POE (Predict-Observe-Explain) oriented Chemoentrepreneurship to understanding the concept and. This research was conducted in MAN 2 Praya, the population in this research was student of MIA class XI, sample was taken by using saturated sampling technique. The design of this research is prettes-posttest control group design. The instruments used to measure conceptual understanding were measured using objective tests. Hypothesis testing was performed by using One-Way ANOVA test with SPSS 15.0 for windows. Based on the results of the study can be concluded that: Application of learning model of POE (Predict-Observe-Explain) oriented Chemoentrepreneurship influence to understanding student concept. This is evidenced by the sig value. of 0.00 < 0.05.